IMPACT OF THE COVID-19 PANDEMIC ON POULTRY FEED DISTRIBUTION IN LIMA PULUH KOTA DISTRICT, WEST SUMATRA PROVINCE - Widya Satya Nugraha; Tulus Fernando Silitonga; Bunga Putri Febrina; Adli Putra Ermanda; Ruth Dameria Haloho; Irmayanti Irmayanti; Nita Adilla Pratiwi; Agni Ayudha Mahanani (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
Since the outbreak of the COVID-19 pandemic in Indonesia, on March 31, 2020, the government of the Republic of Indonesia has adopted a new policy known as PSBB (Pembatasan Sosial Berskala Besar) commonly known as "lockdown". Fulfillment of animal feed ingredients in West Sumatra Province which is still met from outside the province causes disruption of animal feed distribution during the PSBB. This research was conducted by interviewing 50 farmers during the PSBB policy. The data was collected from observations on maintenance. feed ingredients availability, as well as feed ingredients prices. According to the findings of this survey, there was a change in each variable. For example, in the variable transportation of chicken feed materials, 74% of respondents stated that it was smooth during PSBB and reduced by 56% during PSBB. Meanwhile, for the variable availability of chicken feed ingredients, 92% of respondents stated that when the PSBB was adopted, respondents' answers were reduced to 78%, and for the last variable, 24% of respondents stated that feed prices had climbed and treatment. In Indonesia, 76% of respondents said there was no change in prices before and after the PSBB policy was implemented in Lima Puluh Kota Regency, Province of West Sumatera.